Migrant Workers' Willingness to Participate in Workplace Health Promotion Programs: The Role of Interpersonal and Political Trust in China - Xinru Huang (Frontiers Media S.A., 2020)
High-level willingness to participate in WHPPs (Workplace Health Promotion Programs) can not only benefit employers and employees, but also can produce many positive social effects. In order to expand the existing body of research, the effects of subject cognition, interpersonal trust, political trust, and occupational safety and health concerns were explored. We surveyed 680 Chinese migrant workers who were in charge of participation decisions in their households (2,500 residents involved) from the three typical provinces. The association of social-economic determinants with the willingness to participate and the participating behavior was studied by logistic regression analysis. We find that almost all of workers show relatively high levels of willingness to participate, while nearly seventy percent of the migrant workers had not engaged in actual participation behavior. Regression analyses revealed that subject cognition, interpersonal trust, political trust, and concern for occupational safety and health were factors significantly influencing participating subjects' willingness to engage in WHPPs. Furthermore, mediation analyses demonstrated that the influence of subject cognition was partially mediated by political trust. The influence of subject cognition was partially mediated by political trust. We discuss why political trust may impact the influence of subject cognition on the willingness to participate. Our results provided important insights for both academic and practical application.